Profiles and potential health risks of heavy metals in polluted soils in NE-Iran. (3rd April 2022) - Taheri, Masumeh; Mahmudy Gharaie, Mohamad Hosein; Mehrzad, Jalil; Stone, Michael; Afshari, Reza
Abstract: Metal contamination of soil is primarily attributed to human activities and there is an increasing need to conduct risk assessments to characterize the nature and magnitude of risks to humans and ecological receptors from these contaminants. Trace metals (As, Sb, Cd, Cr, Pb, Co, Ni, V, Se, Zn, Fe) in soils from the Chelpu region of North East Iran were analyzed by ICP-OES to assess pollution using the geo-accumulation index (Igeo ) and the enrichment factor (EF). The United States Environmental Protection Agency (USEPA) model was applied to calculate human health risk (HHR). Physicochemical and textural properties of the soil including pH, electrical conductivity (EC), organic matter (OM), calcium carbonate equivalent (CCE) were examined in 26 surface and subsurface soils and related to metal levels. Metal concentrations varied considerably [As (7.1–1448.8 mg/kg), Sb (7.7–74.4 mg/kg), Pb (0.6–26.5 mg/kg), Cd (1–2.6 mg/kg), Cr (67.5–527 mg/kg), Co (18.4–42.6 mg/kg), Ni (85.9–548.6 mg/kg), Sr (180.3–670.6 mg/kg), V (85.3–158.4 mg/kg), Se (0.4–3.10 mg/kg), Zn (44.6–104.9 mg/kg), and Fe (29, 400–51, 800 mg/kg)]. The Igeo indicated that soils were moderately polluted with As, Se, Ni, and Co but heavily to extremely contaminated with Sb and Cd compared with natural soils (USEPA). The enrichment factor (EF) values demonstrated that levels of As, Ni, and Co were moderately enriched but levels of Se, Cd, and Sb were substantially enriched. In contrast, Pb, Cr, Sr, V, and Zn levels were low. Using a human health risk assessment approach, non-carcinogen effects (HI >1) through ingestion of 13.04% of soil samples were determined. Carcinogenic effects through the ingestion pathway were observed for As and Cr in 13% and 3.9% of the soil samples, respectively. Organic matter (OM) content was significantly correlated with As (0.461, α = 0.05), Sb (0.605, α = 0.01), and Se (0.552, α = 0.01).